MENINGKATKAN KEMAMPUAN MENGENAL HURUF VOKAL MELALUI MEDIA PUZZLE HURUF BAGI ANAK SLOW LEARNER - Ririn Yustika Sari; Fatmawati Fatmawati; Yarmis Hasan (Universitas Negeri Padang, 2013)
This research is motivated by problems that researchers in the field discovered that the child is a slow learner X grade 1 who can not read. This study aims to improve the ability to recognize vowels slow learner children grade 1 using the medium of letters puzzle. This research is a Single Subject Research (SSR). The design of this study A-B-A. In the baseline condition could only child so the child knows the letter i scored 20%, in the intervention condition were that increasing a child's ability to recognize five vowels (a, i, u , e, o) so that children receive the highest score is 100%, whereas in the baseline condition (A2) after intervention no longer given where the child is better able to recognize all the vowels and children obtain a score of 100%.